Pesantren, Pecinan and Multicultural Education: A Qualitative Case Study of Kauman Pesantren, Lasem, Central Java - Syamsul Hadi; Dewi Anggraeni (Edukasia Islamika, 2021)
This study aims to analyze the values ​​of multicultural education in Pesantren Kuman. In this context identify how the involvement of Pesantren in mainstreaming the spirit of Islamic moderation. Multicultural education can function to strengthen social integration which is caused by identity politics and intolerant actions. The Kauman Islamic Boarding School is one of the pesantren that has inherited the tradition of the old pesantren or salaf in Lasem. The theory used in this study refers to the theory of social dynamics proposed by Piotr Sztompk, especially related to the dynamics of pesantren and the idea of national and multicultural insight. The method used in this research is qualitative with a sociological approach. The results of this study focus on two aspects of forming the value of multicultural education in the Islamic boarding school of Kauman, namely the element of the formation of heterogeneity of students and the historical environment of the Lasem until the existence of Chinatown, and the aspect of values ​​which include; national values ​​(Wathaniyah), Ikram ul dhuyuf values, social values ​​(ijtima'iyah), jam'iyah values ​​or NU's